BOARDING EDUCATION THROUGH THE LSTEAM LEARNING MODEL: A STRATEGIC RESPONSE TO THE DEMANDS OF 21ST CENTURY EDUCATION - Sudrajat, Mahdi (Journal of Higher Education and Academic Advancement, 2025)
Objective: This conceptual article aims to explore how boarding schools can integrate the LSTEAM (Law, Science, Technology, Engineering, Art, and Mathematics) model to develop globally competent students who are ethically grounded and culturally rooted. Method: Through a literature review and contextual analysis, the study investigates the potential for applying the LSTEAM approach within the unique ecosystem of boarding school education. Results: The findings suggest that LSTEAM provides a transformative framework that aligns ethical reasoning, scientific exploration, technological literacy, and creative expression. The study highlights the importance of project-based learning, cultural relevance, and collaborative pedagogy in implementing LSTEAM effectively in a boarding school setting. Novelty: This article contributes to the growing body of knowledge by proposing a holistic educational model for boarding schools, emphasizing the integration of LSTEAM to produce students capable of navigating global challenges while staying connected to their cultural roots. The model promotes a balance between global competence and local cultural awareness, offering new insights into 21st-century educat.